Perancangan Sistem Manajemen Keamanan Pangan ISO 22000:2018 pada PT Megaprint Citra Mandiri - Lie Angela Sugiarto; Jani Rahardjo (Jurnal Titra, 2022)
Food safety is an important issue for PT Megaprint Citra Mandiri because the company produces food packaging and wants to expand production to pharmaceutical packaging. But in reality, the company has not implemented the ISO 22000 food safety standard in the company. This problem can be answered by designing a food safety standard management system ISO 22000:2018. The purpose of this design is to design a food safety management system by fulfilling documents. The first step is to conduct a gap analysis to determine the current condition of the company. Based on the analysis, the company only met 5.7% of the applicable standards according to ISO 22000:2018. Then do the design of documents that are still lacking and make improvements to several documents so that they are in accordance with the existing standard clauses. . After the fulfillment of the documents, a gap analysis is carried out again to measure the improvement of the appropriate documents. Document fulfillment has an impact on the company, which has increased by 85.9% with document fulfillment by 91.6%.